El ilegal enriquecimiento del empleador laboral en relación al código de trabajo del Ecuador - Feijoo Román, María Dolores (2015)
This legal research includes legal legal content, addresses a subject of vital importance in the workplace with regard to breach of duty, illegal enrichment in labor matters. It was developed in the legal field of public law, specifically on the shortcomings that exist in the Labour Code of Ecuador, in relation to illegal enrichment employer incurring unjust enrichment in labor matters. This is a problem that harms the worker does not receive the benefits of the law that correspond to perform their work in private companies where the employer evades the actual payment of utilities, insurance affiliation, among others. This situation violates the labor and social rights of the worker; while increasing the capital of the company tends to rise, since it benefits at the expense of workers, constituting unjust enrichment, the exploitation of workers. Despite being prescribed in the Constitution of the Republic that the law sanctioned unjust enrichment in the workplace, this standard has not been developed in the sanctions regime of the Labour Code, becoming necessary incorporation into the previous regime to ensure labor rights Workers. Our current labor code aims to be fair, because the protective spirit pervades the weaker side, which is the worker, after balancing the unequal conditions existing in an employment relationship. Labor laws are eminently protective worker and not unfair; but on the contrary, to be fairer, more equitable in the employment relationship, and by protecting workers at the huge difference on the employer, which in many cases has no limit in their excessive desire to make a fortune with the sweat of others defrauding labor laws. From the above, I consider it essential to reform the labor system must force the judges to punish such conduct illegal enrichment or turn the administrative authorities involved, impose sanctions on employers who violate workers' rights unjustly enriched at the expense of workers exploited . As mentioned above, it is necessary to establish a legal reform to the Labour Code in order to punish the negative actions of the employer and enforce basic workers' rights as an employee according to the principles established in the Constitution as possible solution to the given problem